Administrasi surat-menyurat merupakan elemen penting dalam operasional institusi pendidikan. Di SMK Perwira Bangsa, proses surat-menyurat masih dilakukan secara manual sehingga menyebabkan keterlambatan distribusi, kesalahan pengarsipan, dan risiko keaman - Ripal, Muhammad Riski; Meidy Fajar Wahyu (PT Triputra Sejahtera Prima, 2025)
Mail management is an essential part of administrative activities in educational institutions. However, at SMK Perwira Bangsa, the correspondence process is still handled manually, leading to several issues such as delayed distribution, filing errors, and high risks to document security. To address these problems, this research developed a web-based mail management system integrated with workflow automation and digital signatures using OpenSSL. The workflow automates the entire correspondence process, from document creation to distribution, while the digital signature ensures document authenticity and integrity through cryptographic technology. The system was developed using the waterfall methodology, covering stages of requirement analysis, system design, implementation, and testing through black-box testing. Test results showed that the system successfully improved administrative efficiency by accelerating letter distribution, reducing document management errors, and enhancing document security through digital signature validation. Additionally, the system includes a real-time document tracking feature to support transparency and administrative monitoring. The use of OpenSSL provides strong security guarantees for document authentication. This system is expected to serve as an effective digital solution for document management in educational institutions and can be adapted by other schools.